Decarboxylase-positive Enterococcus faecium strains isolated from rabbit meat and their sensitivity to enterocins - Lauková, Andrea; Szabóová, Renata; Pleva, Pavel; Buňková, Leona; Chrastinová, Ľubica (Food science & nutrition, 2017)
BACKGROUND: The objective of the study was to determine sensitivity of Enterococcus faecium strains from rabbit meat to enterocins. RESULTS: Twenty-five decarboxylase-positive strains (from rabbit meat) allotted to the species E. faecium by genotypization and by MALDI TOF MS spectrometry identification (evaluation score value range 2.104-2.359; in the range for highly probable species identification-score value 2.300-3.000 and secure probable species identification/probable species identification-2.000-2.299) were studied. Seventeen strains were gelatinase positive. Although they did not produce histamine (HIS), spermidine, and spermine, they produce at least one among seven tested biogenic amines (BAs) in small amounts (2-10 mg/L) or up to very high amounts (>1000 mg/L). Putrescine was produced by two strains. These decarboxylase-positive strains were sensitive to enterocins (Ents). All strains were sensitive to Ent 2019 and Ent 55 (inhibitory activity from 200 to 819 200 AU/mL). Twenty-two strains were inhibited by Ent A(P) and Ent 4231; 20 strains were sensitive to Ent M. CONCLUSION: Our results have spread the basic knowledge related to inhibitory spectrum of enterocins showing sensitivity of decarboxylase-positive strains to enterocins. Protective possibilities of enterocins in meat processing were also indicated.
Keywords: gelatinase; Enterocococci; enterocins; rabbit meat; inhibition effect; Decarboxylase